Testing flax fibers using high-speed bending - E. L. Pashin; A. V. Orlov (Аграрная наука Евро-Северо-Востока, 2023)
The article presents a method of measuring bending rigidity of flax fiber during high-speed bending. This method is an important part of the effort to reduce the dependency on imported cotton. Unlike the standardized testing methods, the suggested approach closer imitates the conditions present during fiber processing and exploitation of fiber products. For evaluation of bending rigidity of flax fiber during high-speed bending there was used the scheme of loading (meeting the factors of Eule – Bernoulli theory) of a sample fixed in a cantilevered way with the following determination of the work done by bending and deformation by interaction with impact pendulum. The value of sample deformation was determined on the basis of the control of moments of the time of angle velocities deformation which took place by operating movement (during the tests) and free movement of the pendulum. The specific feature of determining the time of deformation were more precise calculations: of angle velocity of the pendulum considering the force of resistance to its free movement; of pendulum motion periods at different stages of its movement during its interaction with the sample; of the time of starting and finishing the interaction by sample bending using the method of dichotomy by approximation of angle velocity values; of angle velocity variation at different stages of its movement during its interaction with the sample. These more precise calculations has become the basis of generalized algorithm for determining the bending deformation by interaction with impact pendulum, done by electronic calculator. A hardware-software complex has been created that employs this algorithm to measure and visualize both sample deformation and pendulum energy loss, as well as angular velocity of the pendulum. A comparison of different kinds of natural bast fibers has been performed – specifically, flax, nettle and hemp. The bending rigidity of these samples has been determined to be 1.42, 2.53 and 6.45 newton‧mm2 accordingly. These differences match the well-known properties of those materials.